Higienização das mãos no cuidado de pacientes infectados ou colonizados com acinetobacter - Silva, Sandra Regina Bin (2014)
Hand hygiene is a primary action in the control of infections caused by multidrug-resistant nosocomial pathogens. However, the efficacy of agents commonly used in hand hygiene in hospital practice has been little investigated. To compare the efficacy of hand hygiene with plain liquid soap, chlorhexidine, ethyl alcohol and alcohol gel for removing Acinetobacter spp from contaminated hands. The study was carried out with 12 patients admitted to the ICU of a teaching hospital, colonized or infected with multidrug-resistant Acinetobacter spp, from May 2011 to September 2012. Bed bath and changing of bandages were the care procedures chosen for the study as the experimental model of hand contamination (N=44). Hand sampling was made by gentle pressure and slipping of fingers on a MacConkey agar plate surface, on the following moments: A1, after hand hygiene before the care procedure; A2, with gloves on; A3, with gloves on after the care procedure; A4, with gloves on after hand hygiene with the products tested; A5, hands after gloves removal; A6, after final hand hygiene with water and soap. The plates with MacConkey agar were incubated at 37ºC, in aerobiosis, during 24-48 hours. Morphologic and staining properties of the cells of at least one different type of colony per plate were investigated by the Gram?s stain method. The identification and antibiogram of the colonies selected for study were performed by the MicroScan® identification system. A laboratory study, using a Latin square 5x5, to assess the efficacy of soap, chlorhexidine and alcoholic preparations for removing a clinical isolate of a multidrug-resistant A. baumannii from artificially contaminated hands, was also performed. There was bacterial growth in 15% (76/528) of the plates used for the hand sampling. From the preliminary study (colonial morphology and Gram?s stain) 119 typical and atypical colonies were selected for identification. Acinetobacter baumannii contributed with 66 (55%) of the isolates, Enterobacteriaceae with 28 (23%), Pseudomonas aeruginosa with 16 (13%), Acinetobacter spp with 7 (6%), and others with 2 (1.6%). In A3, A. baumannii was detected in 42 of the 44 (95.45%) samplings. In A4, alcohol gel removed A. baumannii from gloved hands after contact with 11 (92%) patients, ethyl alcohol and soap did it after contact with 10 (83%) patients, and chlorhexidine in only two (17%) out of 12 patients. In A5, Acinetobacter spp were isolated in two (4.5%) out of 44 samplings. The laboratory study showed that alcohol gel and ethyl alcohol presented greater efficacy than chlorhexidine and soap for removing A. baumannii from hands artificially contaminated (p < 0.05%). The results showed that alcohol gel, ethyl alcohol and soap were the most effective products in removing multidrug-resistant A. baumannii isolates from contaminated hands in hospital practice. The laboratory study confirmed the superiority of alcohol gel and ethyl alcohol in the antisepsis of hands contaminated with multidrug-resistant A. baumanni.